Pendampingan Pendalaman Materi dan Pelatihan Pengembangan Konten Pembelajaran IPA Bagi Guru-Guru IPA di Desa Huntu Kecamatan Batudaa - Mursalin Mursalin; Citron S Payu (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
Thematic Work Lecture Program of Building Village aims to train teachers in Batuda'a Subdistrict to be able to develop IPA learning content. Through this program, it is expected that field guidance lecturers and students will jointly collaborate to help teachers in developing IPA learning content. In addition, with the Real Work Lecture (KKN) program, Thematic Village Building students are expected to plunge into society, interact, socialize, and cooperate with the community. In this program, activities will be focused on training and fostering teachers in Batuda'a Sub-District to be able to develop IPA learning content. This activity was held in Huntu Village, Batudaa Subdistrict, Gorontalo Regency, and was integrated with Real Work Lecture (KKN), Research and Community Service Institute (LPPM) of Gorontalo State University (UNG) in 2021. This activity is supported directly by the Huntu Village apparatus, led by the Huntu Village Chief as a partner in this program.